Quels sont les effets de l'éducation artistique ? Étude d'une situation paradoxale - Virginie Ruppin (Nantes Université, 2010)
It seems that art education has an effect on people. What effect can appear in artistic activities in an institution, but also on people living there? What happens when artists come to a primary school? Sociology of justification and objects delegation can help us to explain many interview points and to better analyse observation in the classroom.Through the example of an artistic and cultural music project carried out in a class of children of ten year olds, we realized, contrary to all expectations, that the setting up of the project had a tendency to reinforce rules of behaviour. In fact, the discourse reveals that the teacher uses music at school rather as a means of discipline in his class, instead of using it to develop expression, creation and the development of children.